Hierarchical Polyamide 6 (PA6) Nanofibrous Membrane with Desired Thickness as Separator for High-Performance Lithium-Ion Batteries. Issue 7 (1st January 2017) - Chen, Jiahui; Liu, Qiongzhen; Wang, Bo; Li, Fei; Jiang, Haiqing; Liu, Ke; Wang, Yuedan; Li, Mufang; Lu, Zhentan; Wang, Dong
Abstract : Polymeric nanofibrous separators have drawn a great attention due to their unique tortuous pores for preventing the growth of lithium dendrites and hence ensuing high safety and cycling stability. Various nonwoven mats with strong mechanical strength are typically served as substrate materials for nanofibrous membranes. However, the overall thickness (>40 μm) of most nanofibrous separator is far beyond the ideal dimension (25∼30 μm), thus severely reducing the energy densities of batteries. In present work, a hierarchically structured polyamide 6 (PA6) nanofibrous separator (designated as PA6/PET/PA6) with a desired thickness of 30 μm has been successfully developed using an ultra-thin poly (ethylene terephthalate) (PET) nonwoven (18 μm) as the substrate. Due to the flatness and hydrophobic nature, surface modifications of PET nonwoven have been attempted to improve the adhesion force between PET and PA6 membranes by NaOH solution treatment. The resultant PA6/PET/PA6 separator exhibits lower thermal shrinkage, higher electrolyte affinity and ionic conductivity, as well as superior rate capabilities and cycling performance compared with commercial PP separator, suggesting a promising candidate for practical application in high-rate LIBs.